Crow smarts : inside the brain of the world's brightest bird - Turner, Pamela S. (Scientists in the field., 2016)
"In the newest addition to the ever-popular and authoritative nonfiction Scientists in the Field series, the team behind The Frog Scientist take you on a research trip to New Caledonia in the Pacific Ocean to follow crows in aviaries and in the wild while answering many thought-provoking questions like: "Can a crow outsmart a scientist?" Remarkably engaging narrative nonfiction coupled with beautiful photographs, this is a trip you won't regret booking!"--